Adam Sharp : London Calling - Stanley, George Edward; Francis, Guy (New York : Random House, 2003)
Eight-year-old superspy Adam Sharp is summoned to cowboy-infested London to find out who stole Big Ben.
Keywords: Spies -- Fiction; Cowboys -- Fiction; Juvenile literature; London (England) -- Fiction; England -- Fiction